2002
DOI: 10.1002/mus.10183
|View full text |Cite
|
Sign up to set email alerts
|

Partial conduction blocks in N‐hexane neuropathy

Abstract: Nerve conduction blocks, defined by a significant reduction in amplitude or area of the compound muscle action potential at proximal compared with distal sites of stimulation, have been described in glue-sniffers and in workers with industrial exposure at an early stage of n-hexane neuropathy. The frequency with which this focal conduction anomaly appears is described and discussed in the case of a very homogeneous group of 10 young workers diagnosed with n-hexane polyneuropathy. Partial conduction blocks occu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(14 citation statements)
references
References 14 publications
1
12
1
Order By: Relevance
“…Conduction blocks were seen. On needle electromyography (EMG), the features of denervation have been seen in all the patients in a previous study [6,[14][15][16]. Also in our patient there were features suggestive of sensorymotor neuropathy with a conduction block in bilateral common peroneal nerves and absence of conduction in bilateral sural nerves.…”
Section: Vertigo and Cold Allodynia In N-hexane Neuropathy C A S E R supporting
confidence: 75%
“…Conduction blocks were seen. On needle electromyography (EMG), the features of denervation have been seen in all the patients in a previous study [6,[14][15][16]. Also in our patient there were features suggestive of sensorymotor neuropathy with a conduction block in bilateral common peroneal nerves and absence of conduction in bilateral sural nerves.…”
Section: Vertigo and Cold Allodynia In N-hexane Neuropathy C A S E R supporting
confidence: 75%
“…Exposure may occur with the use of degreasing solvents and cleansers, and after intentional inhalation of household glues for intoxication [16,17]. Chronic exposure may result in a distal sensory motor neuropathy, whereas acute exposure may lead to predominantly motor and cranial nerve features.…”
Section: Environmental Toxinsmentioning
confidence: 99%
“…Chronic exposure may result in a distal sensory motor neuropathy, whereas acute exposure may lead to predominantly motor and cranial nerve features. Focal conduction block may be present on neurophysiologic assessment [16]. Giant axonal swellings consisting of neurofi lamentous aggregates are the classic neuropathologic fi nding in N-hexane neuropathy [15•].…”
Section: Environmental Toxinsmentioning
confidence: 99%
“…1,2 Development of hexacarbon neuropathy as a result of nhexane exposure was first recognized and reported in the 1960s. 2 N-hexane is a petroleum product used in solvents and glues and is associated with occupational neuropathies seen in automobile mechanics, 2 shoe-makers, 3,4 purse makers 5 and furniture finishers. 4 Toxicological studies of n-hexane have shown that this solvent causes peripheral neuropathy in both experimental animals and humans.…”
Section: Introductionmentioning
confidence: 99%